Attitudes of Greek Undergraduate Students Towards Issues of Fraud and Plagiarism during Their Studies - Maria, Melikidou; Kyridis, Argyris (International Journal of Learning and Development, 2024)
This research aimed in revealing attitudes of Greek undergraduates’ students towards issues of fraud and plagiarism during their studies. That’s because there are many cases where students choose to copy from others or to cheat in their exams and it’s something that many universities try to overcome and avoid. The sample of our study consisted of 250 people studying in various faculties of Greek universities throughout the country. Their answers were analyzed in a questionnaire using both descriptive and inferential statistics. Students’ answers revealed that almost all students at least once in their lifetime have cheated or copied in their homework or in their exams, even though the majority of them knew the effects that plagiarism has in the university community. They state that there are many reasons that have led them there with the most frequent ones being the lack of time, the pressure from the multitude of obligations, the absence of strict controls from the teachers and their desire to succeed.